Projeto de prevenção de incêndio em edificações existentes: um comparativo entre as normas do Paraná e Santa Catarina - Fianco, Mariana Masiero (2021)
Fire prevention and fight ing was introduced late in Brazil, it was after the event of tragedies that have changed these conditions and it is recent the mandatory fire prevention and fighting project in buildings. Consequently, it can be founded, buildings located in the center of the cities that do not have this project, endangering the user population and buildings in its surroundings. Because of this, two downtown buildings were chosen from the city of Pato Branco – Paraná, who did not have a project, and carried out the sizing them according to the laws and standards of the state of Paraná and Santa Catarina, to analyze the singularities and differences between them. After performing the proper classifications and dimensioning of the required security measures, it can be concluded that there are divergences between them, some more expressive than others but, leave doubts about project sizing.